Section 106 of the Law Reform (Marriage and Divorce) Act 1976 of Malaysia: issues and suggestions - Md Hashim, Noraini; Abdul Hak, Nora; Rahmat, Nur Ezan (INSI Publications, 2012)
Dispute resolution outside the court is not new in human interactions. Different societies across the world have long used non-judicial indigenous methods to resolve conflicts. Family disputes, more often than not, are rarely concerned with matters of fact but are almost invariably complicated by the intense and intimate emotions of the parties in conflict. Therefore, the utilization of other processes, such as conciliation and mediation, will lead to a more satisfactory resolution of disputes rather than the prevailing practice of litigation. Section 55(2) of the Law Reform (Marriage and Divorce) Act 1976 (LRA1976) provides that even when the parties have presented a petition for divorce, if it appears to the court at any stage of the proceedings that there is a reasonable possibility of a reconciliation between them, the court may adjourn the proceedings for such period as deems fit to enable attempts to be made to effect such a reconciliation. In the case of a petition for divorce based on the irretrievable breakdown of the marriage, the petitioner must first refer the matrimonial difficulty to a conciliatory body before filing the petition in accordance with sections 51 and 52 of LRA. Practitioners of family law are of the view that the conciliation process in Malaysia has not been very successful in helping disputing couples resolve their problems and this is supported by statistics, which shows that the success rate recorded at the statutorily mandated reconciliation sessions is very low. This article examines some emerging issues relating to the effectiveness of conciliatory bodies appointed under section 106 of LRA 1976, especially the effectiveness of the marriage tribunal under the National Registration Department. It highlights the problems and constraints faced by the conciliatory bodies, and suggests some law and policy reforms.